Cost-effectiveness of early nutritional therapy in malnourished adult patients in a high complexity hospital (2015)
ABSTRACT: hospital malnutrition is a frequent worldwide problem and its potential issues related include increased complications, length of stay, mortality, and healthcare costs. Objectives: the aim of this study was to establish the cost-effectiveness of early nutritional therapy for mal-nourished patients in a high complexity hospital. Materials and methods: this analytical study with economic assessment included 227 adult hospitalised and malnourished according to the Subjective Global Assessment. The cohort prospective received Early Nutrition Therapy (ENT), whereas the cohort retrospective received Delayed Nutrition Therapy (DNT). The measures of cost-effectiveness included costs by: length of stay, complications and discharge condition. Results: the cohorts were similar in demographic and clinical characteristics, except that the median age, for the ENT was 61 years (interquartile range [IQR]: 48-71) and for the DNT was 55 years (IQR: 44-67) (p = 0.024). The median length of stay was lower in the ENT (11 days, IQR: 7-17) than in the DNT (18 days, IQR: 10-28) (p < 0.001). The cost per patient discharged alive was US $ 10,261.55 in the ENT and US $ 15,553.11 in the DNT (p=0.043); the cost per patient with complications was US $ 13,663.90 in the ENT and US $ 17,860.32 in the DNT (p= 0.058). ENT increased the likelihood of being discharged alive, RR adjusted=0.31; 95% confidence interval (CI): 0.1; 0.6; (p<0.001) and decreased the likeli- hood of complications RR crude=0.8; 95% CI: 0.6; 0.9; (p=0.006).